Visual communication in public space through mural art in Makassar, Indonesia - Wasilah Sahabuddin; Andi Hildayanti (SINERGI, 2024)
Mural art serves as a powerful means of visual communication, allowing artists to convey messages, narratives, and ideas through visual elements. Murals often address social, political, cultural, or environmental issues, expressing viewpoints and sparking conversations within the community. This study aims to examine the role and meaning of visual communication in mural art in Makassar City. The object of observation is divided into two, namely mural art that is appropriate in its place and mural art that is not in its place, such as the walls of inhabited houses, shop fences, and public facilities. Through the case study research method conducted in the city of Makassar, the data collected through the observation and interview stages were then analyzed descriptively. The results show that mural art is an alternative form of conveying messages through aesthetic and ethical values. Due to its significant role in arousing one's feelings, the Makassar city government has made mural art an indicator of improving the quality of the city's environment through the Lorong Wisata program. As part of the "Lorong Wisata" program, mural art can be commissioned or encouraged to enhance the visual appeal of the designated lanes. Murals can transform plain walls into vibrant and visually captivating artworks, adding color and character to the surroundings. Mural installations can serve as focal points and landmarks within the tourism lanes, attracting visitors and providing unique photo opportunities.